2005
DOI: 10.1002/jmv.20369
|View full text |Cite
|
Sign up to set email alerts
|

Alternative EBNA1 expression in organ transplant patients

Abstract: In order to identify patients at risk for developing post-transplant lymphoproliferative disease (PTLD), a sensitive nested RT-PCR method for detection of EBNA1 gene expression in peripheral blood cells was used. EBNA1 expression in peripheral blood samples from 60 organ recipients was analyzed and compared with 24 healthy controls in a retrospective study. Overall, EBNA1-positive samples were detected at least once in 43% of the transplant patients with post-transplant lymphoproliferative disease, in 18% of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Alternative splicing including long-range exon skipping in the 5 0 untranslated region upstream of the EBNA1-encoding K exon generates the EBNA1 mRNA. A functional alternative splice in the EBNA1 transcript that omits the U exon and consequently exclude the EBNA IRES element was recently reported [Berggren et al, 2005]. Transfection and Western blot experiments with an EBNA1 coding plasmid confirmed that the EBNA IRES promotes capindependent translation and increases the EBNA1 protein level.…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…Alternative splicing including long-range exon skipping in the 5 0 untranslated region upstream of the EBNA1-encoding K exon generates the EBNA1 mRNA. A functional alternative splice in the EBNA1 transcript that omits the U exon and consequently exclude the EBNA IRES element was recently reported [Berggren et al, 2005]. Transfection and Western blot experiments with an EBNA1 coding plasmid confirmed that the EBNA IRES promotes capindependent translation and increases the EBNA1 protein level.…”
Section: Introductionmentioning
confidence: 64%
“…Furthermore, analysis of the EBNA1 expression in peripheral blood samples from solid organ transplant patients revealed an alternatively spliced form of the EBNA1 transcript, which excludes the EBNA IRES element. The alternative transcript was expressed in the majority of the investigated EBNA1-positive organ transplant patient samples as well as in some EBVpositive cell lines [Berggren et al, 2005]. The presence of an IRES element within the EBV constitutes additional possibilities for the virus to regulate its gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations